2018
DOI: 10.1177/1350507618759828
|View full text |Cite
|
Sign up to set email alerts
|

Imagining management education: A critique of the contribution of the United Nations PRME to critical reflexivity and rethinking management education

Abstract: Imagining management education: a critique of the contribution of the United Nations PRME to critical reflexivity and rethinking management education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 33 publications
(51 reference statements)
1
61
0
3
Order By: Relevance
“…Within the responsible management education literature, there have been discussions regarding the barriers to change and transformation, particularly in the context of Principles of Responsible Management Education (PRME) and Business School curricula (Solitander et al 2012;Cornuel and Hommel 2015a;Rasche and Gilbert 2015;Millar and Price 2018). However, there has been relatively less work assessing responsible management learning within the workplace, resulting in a "skewed focus on responsible management education" (Laasch and Gherardi 2019, p. 2) and has led to calls for "a shift in emphasis of future research on responsible management and responsible management learning" (Laasch and Gherardi 2019, p. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Within the responsible management education literature, there have been discussions regarding the barriers to change and transformation, particularly in the context of Principles of Responsible Management Education (PRME) and Business School curricula (Solitander et al 2012;Cornuel and Hommel 2015a;Rasche and Gilbert 2015;Millar and Price 2018). However, there has been relatively less work assessing responsible management learning within the workplace, resulting in a "skewed focus on responsible management education" (Laasch and Gherardi 2019, p. 2) and has led to calls for "a shift in emphasis of future research on responsible management and responsible management learning" (Laasch and Gherardi 2019, p. 2).…”
Section: Introductionmentioning
confidence: 99%
“…Burchell, Murray & Kennedy (2014), also in the UK business school context, questioned the existence of direct evidence of PRME in driving changes in curricula. These themes were further amplified in recent work by Millar and Konig (2018) and Millar and Price (2018), also focusing on the UK PRME signatory context, that found that PRME reproduced a dominant market ethic and was not able to produce a critical reflexivity necessary to drive fundamental transformations in management education, respectively. These critical studies point us toward contextual variables that may adversely impact or even sabotage PRME implementation.…”
Section: Scholarly Literature About Prmementioning
confidence: 97%
“…& Herlin, 2012;Young and Nagpal, 2013), barriers to implementation (for initial statements, see: Maloni, Smith & Napshin, 2012;Solitander, Fougère, Sobczak. & Herlin, 2012;and Cornuel & Hommel, 2015), and also critiques of PRME and its implementation in various business schools (Louw, 2014;Millar and Konig, 2018;and Millar & Price, 2018). What has been less well studied, at least systematically, has been predictors and/or correlates of PRME commitment and involvement across individual faculty.…”
Section: Introductionmentioning
confidence: 99%
“…The varying interpretations of RME are illustrated by the inconsistent ways in which RME is being institutionalised in Business Schools (Burchell, Kennedy, and Murray 2015;Doherty, Meehan, and Richards 2015). While some business schools have undertaken substantive changes, including making strategic commitments to the RME agenda (Millar and Price 2018), others have engaged in RME in an ad hoc manner (Khurana and Spender 2012;Nonet, Kassel, and Meijs 2016;Warin and Beddewela, 2016) thereby adopting more 'reactive' strategies (Cornelius, Wallace, and Tassabehji 2007;Jamali, Abdallah, and Matar 2016). This further complicates the ability to replicate a constructive process of change for RME institutionalisation at the intra-organisational level, or follow one elsewhere, with any degree of success (Doh and Tashman 2014).…”
Section: Responsible Management Educationmentioning
confidence: 99%
“…Although there is a spectrum of views on these matters, there is widespread acknowledgement by academicians that a major transformation is required of business schools if they are to create managers who are prepared to deal with the critical global challenges facing business and society in the twenty-first century, including sustainability and social justice (Millar and Price 2018;Doherty, Meehan, and Richards 2015). One proposed solution is for business schools to reposition themselves by adopting a more human-centred worldview, which recognises the interconnectedness of a larger societal system in which business represents only one component (Nonet, Kassel, and Meijs 2016;Giacalone and Thompson 2006).…”
Section: Introductionmentioning
confidence: 99%